The Effectiveness of Learning Two Stay Two Stray to Reduce Cognitive Load Accordance Student Learning Styles - Munandar, Rifki Risma; Rahmat, Adi; Hidayat, Topik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research is motivated by the lack of effectiveness in the learning process in receiving and processing information to acquire reasoning abilities as students still had cognitive load. The purpose of this study was to determine the effect of learning for two stay two stray on Spermatophyta material to decrease the intrinsic cognitive load corresponding student's learning style. The method used is a quasi-experimental design with posttest only. The subjects were high school students of class X IPA at SMAN 7 Bandung. Control class (34 students) using conventional pembalajaran strategies and experimental classes (33 students) teaching methods two stay two stray. The research instrument used in the form of essay that describes the students' reasoning ability and task complexity are arranged in the form of questions in worksheet students to determine the ability to receive and process information. Data were analyzed by using a different test average and correlation test. The results of the calculation of average ability to receive and process information on the audio learning styles experimental class is higher than the control class. In the experiment class decline intrinsic cognitive load correlated with increased learning outcomes for students with learning style audio. These results illustrate that the use of learning strategies two stay two stray has lowered the intrinsic cognitive load of students who have learning style audio.Keywords: cognitive load, learning styles and learning methods two stay two stray